Analysis of the Impact of the COVID-19 Pandemic and Gross Domestic Product (GDP) on Stock Transaction Volume and Stock Prices in the Tourism Company Group Listed on Indonesia Stock Exchange in 2018-2023 - Sitanggang, Jona Steven; Aulia, Ando Fahda; Darmayuda, Darmayuda (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
This study aims to analyse the effect of COVID-19 and Gross Domestic Product (GDP) on the volume of stock transactions and stock prices in the tourism company group listed on the IDX in 2018-2023. This study uses quantitative research methods with panel data analysis and is processed using Eviews 12. The dependent variable is the volume of stock transactions and stock prices. The independent variables in this study are the value of Gross Domestic Product (GDP) and COVID-19, which are used as dummy numbers. This research shows that COVID-19 has a significant negative effect on the price of shares and a significant positive effect on the volume of stock transactions. Meanwhile, Gross Domestic Product (GDP) does not affect changes in stock prices or stock transaction volume.